2010
DOI: 10.1007/s12098-010-0327-3
|View full text |Cite
|
Sign up to set email alerts
|

Pain Response in Newborns to the Order of Injecting BCG and Hepatitis-B Vaccines: A Randomized Trial

Abstract: Pain was reduced when the BCG vaccine was administered before the Hepatitis-B in neonates undergoing routine vaccination. The authors recommend that the order of vaccine injections be the BCG vaccine followed by Hepatitis-B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…Two trials including infants in the first 6 months of life investigated the effect of injecting the most painful vaccine last. 13 , 14 Included studies compared either: (1) pneumococcus conjugate vaccine, PCV (Prevnar) to diphtheria and tetanus toxoids, polio, acellular pertussis, and Haemophilus influenzae type b conjugate vaccine, DPTaP-Hib (Pentacel), or (2) Bacille Calmette-Guérin vaccine, BCG (Tubervac) to hepatitis B vaccine (GeneVac-B). There was moderate quality evidence for distress, the critical outcome (see Table, http://links.lww.com/CJP/A283 SDC 2).…”
Section: Resultsmentioning
confidence: 99%
“…Two trials including infants in the first 6 months of life investigated the effect of injecting the most painful vaccine last. 13 , 14 Included studies compared either: (1) pneumococcus conjugate vaccine, PCV (Prevnar) to diphtheria and tetanus toxoids, polio, acellular pertussis, and Haemophilus influenzae type b conjugate vaccine, DPTaP-Hib (Pentacel), or (2) Bacille Calmette-Guérin vaccine, BCG (Tubervac) to hepatitis B vaccine (GeneVac-B). There was moderate quality evidence for distress, the critical outcome (see Table, http://links.lww.com/CJP/A283 SDC 2).…”
Section: Resultsmentioning
confidence: 99%
“…Of the two vaccines, BCG is given by intradermal route and hepatitis B is given by intramuscular route. Pain during intramuscular route is significantly higher than the pain due to in the intradermal route (12) . This can be explained by the fact that needle used for intramuscular injection is of wider bore as compared to that used for intradermal route.…”
Section: Discussionmentioning
confidence: 93%
“…In a study in Karnataka, India, vaccine administration order of intradermal Bacille Calmette-Guérin (BCG) and intramuscular Hepatitis-B vaccines in term neonates were evaluated and the result showed that overall pain scores which were measured by the Neonatal Infant Pain Scale was lower when BCG vaccine was injected first and Hepatitis-B vaccine thereafter [11].…”
Section: Discussionmentioning
confidence: 99%